Pengaruh Konten “JakiMaulana” terhadap Informasi dan Minat Kunjung: Survei pada Followers Akun TikTok @Cecilianov - Qori'ah, Nadiatul; Delima, Isniyunisyafna Diah; Salsabil, Luna Safitri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Cecilianov is a TikTok influencer who shares his experiences traveling using public transportation in his content called "JakiMaulana" (Walking to wander). This research was conducted to find out how much influence "JakiMaulana" content has on information and interest in visits, especially for followers of the TikTok account @cecilianov. The theory used in this research is the S-R (Stimulus-Response) theory. The S-R theory is used by the author to show the process and also the consequences caused by the content of "JakiMaulana". This research uses a descriptive quantitative method with a sample of 100 respondents taken using a purposive sampling technique. The research results show that the content of "JakiMaulana" (X) has a positive and significant influence on information (Y1) and visiting interest (Y2). Hypothesis Ha is accepted and H0 is rejected, which means that the content of "JakiMaulana" (X) has a significant effect on the Information variable (Y1) and also has an effect on visiting interest (Y2).